2017
DOI: 10.21164/pomjlifesci.278
|View full text |Cite
|
Sign up to set email alerts
|

Budowa bariery jelitowej

Abstract: The intestinal barrier consist of several layers. It is made of gut microbiota, a protective layer of mucus, intestinal epithelial cells, and the blood, lymphatic, immune and nervous systems. Mucus, which prevents the adhesion and penetration of pathogens to the intestinal wall, is also a habitat for intestinal microbiota -one of the key and most dynamic elements of the intestinal barrier. Microbiota mainly consist of anaerobic bacteria, and also aerobic bacteria, yeast and viruses. The intestinal ecosystem is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…Zawiera ona substancję przeciwbakteryjne działające na bakterie patogenne oraz immunoglobuliny A. Kolejną warstwę stanowi jedna warstwa komórek nabłonkowych, która zawiera głównie enterocyty, komórki kubkowe, komórki układu odpornościowego (w tym komórki Panterha) i endokrynnego. Pomiędzy komórkami znajdują się połączenia ścisłe, którym przypisuje się główną rolę w nieszczelności jelit [39]. Jak już wcześniej wspomniano, u osób z otyłością dochodzi do dysbiozy, czego wynikiem może być zwiększony odsetek bakterii gram ujemnych.…”
Section: Zmiany W Mikroflorze Związane Z Otyłościąunclassified
“…Zawiera ona substancję przeciwbakteryjne działające na bakterie patogenne oraz immunoglobuliny A. Kolejną warstwę stanowi jedna warstwa komórek nabłonkowych, która zawiera głównie enterocyty, komórki kubkowe, komórki układu odpornościowego (w tym komórki Panterha) i endokrynnego. Pomiędzy komórkami znajdują się połączenia ścisłe, którym przypisuje się główną rolę w nieszczelności jelit [39]. Jak już wcześniej wspomniano, u osób z otyłością dochodzi do dysbiozy, czego wynikiem może być zwiększony odsetek bakterii gram ujemnych.…”
Section: Zmiany W Mikroflorze Związane Z Otyłościąunclassified
“…On the other hand, the outer part of mucus is of low density and rich in immunoglobulins. It forms a habitat for mucolytic bacteria such as Akkermansia muciniphila, Bacteroides thetaiotaomicron and Bacteroides fragilis [14][15][16][17][18]. Parikh et al observed that in UC, a protein with antimicrobial activity (WAP Four-Disulfide Core Domain 2 -WFDC2) secreted by goblet cells causes mucus defects by reducing its expression [19].…”
Section: Intestinal Homeostasismentioning
confidence: 99%
“…The intestinal barrier consists of a single layer of epithelial cells (mainly enterocytes) connected by tight junctions (TJ), which seal the intercellular space [1] Absorption in the intestinal epithelium is highly selective. Such selective absorption is an unquestionable advantage of the intestinal barrier and it is closely linked to its complex structure.…”
Section: Introductionmentioning
confidence: 99%